Rubber for diamond wire saw, preparation method thereof and diamond wire saw using the same
By using natural rubber and functional additives in the rubber for diamond wire saws, as well as the addition of multi-balance agents and modified fillers, the problem of poor coordination of existing rubber performance has been solved, significantly improving wear resistance and tear resistance and flexural performance improves cold and cold resistance and acid and corrosion resistance, and improves the efficiency of use.
Patent Information
- Application Number
- CN202411563007.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing rubber for diamond wire saws has poor tear resistance, and the wear resistance, tear resistance and flexural properties are difficult to coordinately improve. The product has poor heat resistance and acid corrosion resistance, which limits the efficiency of use.
Natural rubber is used to combine carbon black N330, silane coupling agent, sulfur, accelerator, stearic acid and anti-aging agent as functional additives, and coordinate and coordinate the combination by adding multi-adjustment balance agent and modified filler agent, and work together. Improve product performance.
The wear resistance, tear and flexural properties of the rubber for diamond wire saws are significantly improved, coordination and performance stability, the product's resistance to heat and acid and corrosion resistance are improved, and the use efficiency is improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diamond wire saws, and in particular to a rubber for a diamond wire saw, a preparation method thereof and a diamond wire saw using the rubber. Background Art
[0002] Diamond wire saws are widely used in mining and processing, stone plate cutting, reinforced concrete component sawing and other fields. Diamond wire saws include diamond beads, wire ropes and rubber. Diamond beads are the core components of diamond wire saws and are responsible for cutting operations; wire ropes play a role in connecting and increasing tension in diamond wire saws; rubber is mainly used in diamond wire saws to reinforce beads to prevent them from loosening during work.
[0003] The existing rubber for diamond wire saw has poor tear resistance, and it is difficult to coordinate and improve the wear resistance, tear resistance and flexural properties of the product. In addition, the product has poor stability in heat and cold resistance and acid corrosion resistance, which limits the use efficiency of the product. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a rubber for a diamond wire saw, a preparation method thereof and a diamond wire saw using the rubber, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a rubber for a diamond wire saw, comprising the following raw materials in parts by weight:
[0007] 35-40 parts of natural rubber, 10-15 parts of multi-adjusting balance agent, 4-7 parts of modified filler, 5-8 parts of carbon black N330, 3-5 parts of silane coupling agent, 2-4 parts of sulfur, 1-3 parts of accelerator, 1-3 parts of stearic acid, and 1-3 parts of antioxidant.
[0008] Preferably, the natural rubber is No. 3 smoked rubber; the silane coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 4020; and the accelerator is accelerator TMTD.
[0009] Preferably, the preparation method of the multi-adjusting balancing agent is:
[0010] S01: Stir and mix the nano-attapulgite in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry to obtain dry nano-attapulgite;
[0011] The dried nano-attapulgite is calcined at 220-230° C. for 20-30 min, then cooled to 55° C. at a rate of 2-5° C. / min, and kept warm to obtain calcined nano-attapulgite;
[0012] S02: Add 3-5 parts of nano titanium dioxide and 1-2 parts of carboxymethyl cellulose to 5-8 parts of modified chitosan agent by weight, and then add 2-4 parts of wollastonite, and mix well to obtain a blending synergist;
[0013] Wherein, the preparation method of modified chitosan agent is:
[0014] A chitosan solution with a mass fraction of 3-6% is prepared, and a sodium silicate solution with a mass fraction of 4-7% of the total weight of the chitosan solution and a sodium lignin sulfonate with a mass fraction of 2-4% of the total weight of the chitosan solution are added to the chitosan solution and mixed sufficiently to obtain a modified chitosan agent;
[0015] S03: The calcined nano-attapulgite and the blending synergist are ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1200-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a multi-tuning balancing agent.
[0016] Preferably, the mass fraction of the sodium silicate solution is 5-7%.
[0017] Preferably, the preparation method of the modified filler is:
[0018] S11: The nano-calcium carbonate is firstly mixed in a 5% sodium citrate solution having a mass fraction of 3 to 5 times the total weight of the nano-calcium carbonate, to obtain a nano-calcium carbonate solution;
[0019] S12: adding 2 to 3 parts of nano-silica sol and 1 to 3 parts of silane coupling agent to 5 to 8 parts of lanthanum nitrate solution by weight, stirring and blending them thoroughly to obtain a modified silica sol;
[0020] The nano calcium carbonate solution and the modified silica sol agent are uniformly mixed in a weight ratio of 5:(2-3) to obtain a nano calcium carbonate modifier;
[0021] S13: The nano calcium carbonate modifier and the reinforcing agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1050 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a modified filler.
[0022] Preferably, the mass fraction of the lanthanum nitrate solution is 3-5%; and the silane coupling agent is silane coupling agent KH560.
[0023] Preferably, the preparation method of the reinforcing agent is:
[0024] According to weight, 2-5 parts of calcined talcum powder and 1-3 parts of stearic acid are added to 5-8 parts of dopamine hydrochloride solution, and then 2-3 parts of silicon nitride whiskers and 1-2 parts of yttrium nitrate solution are added and mixed and ball-milled at a speed of 750-850 r / min for 2 hours. After the ball milling is completed, the reinforcing agent is washed with water, filtered and dried to obtain the reinforcing agent.
[0025] Preferably, the mass fraction of the dopamine hydrochloride solution is 3-6%; the mass fraction of the yttrium nitrate solution is 3-5%.
[0026] The present invention provides a method for preparing rubber for diamond wire saw, which is used for preparing the rubber for diamond wire saw, and comprises the following steps:
[0027] The raw materials are weighed according to weight, and then the raw materials are mixed at a mixing temperature of 45° C. for 20 minutes. After the mixing is completed, a mixed material is obtained; the mixed material is placed in a vulcanizer for vulcanization at a vulcanization temperature of 145° C., a vulcanization pressure of 10-15 MPa, and a vulcanization time of 6-10 minutes to obtain a rubber for a diamond wire saw.
[0028] The invention also provides a diamond wire saw, comprising the rubber for the diamond wire saw.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The rubber for diamond wire saw of the present invention adopts natural rubber, carbon black N330, silane coupling agent, sulfur, accelerator, stearic acid and antioxidant as functional additives, and by adding multi-adjusting balance agent and modified filler, the two are coordinated and matched, and the wear resistance, tear resistance and flexural performance of the product are coordinated and improved, and the product has remarkable cold and heat resistance and acid corrosion resistance stability;
[0031] 2. The multi-adjusting balance agent uses nano-attapulgite treated in potassium permanganate solution to optimize its activity performance, and then calcined to further enhance its activity performance. Nano-titanium dioxide, carboxymethyl cellulose, modified chitosan agent and wollastonite are formulated. Through the coordinated addition effect of wollastonite and nano-titanium dioxide, and after the improvement of the modified chitosan agent, the chitosan solution, sodium silicate solution and sodium lignin sulfonate in the modified chitosan agent are coordinated and coordinated to enhance the interface and activity performance between the raw materials of the system. The nano-attapulgite is reinforced by wollastonite with nano-titanium dioxide, so that the performance coordination and performance stability of the system are further improved.
[0032] 3. The modified filler is prepared by using nano calcium carbonate and sodium citrate solution to optimize the dispersion of nano calcium carbonate, and then further coordinated by using modified silica sol. The modified silica sol is fully mixed by stirring nano silica sol, silane coupling agent and lanthanum nitrate solution, and dispersed into the lanthanum nitrate solution system through nano silica sol to enhance the interface effect of the system, so as to facilitate the coordination of the reinforcing agent in the modified filler system with nano calcium carbonate, thereby further improving the product performance;
[0033] 4. The reinforcing agent is made of burnt talcum powder and silicon nitride whiskers. The burnt talcum powder is blended with silicon nitride whiskers with whisker-like structures, and then the mixture is blended and ball-milled with stearic acid, dopamine hydrochloride solution and yttrium nitrate solution. The reinforcing agent obtained by the coordination and matching of the raw materials is a better reinforcing and modified filler, so that the performance of the product is further improved. DETAILED DESCRIPTION
[0034] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The rubber for diamond wire saw of the present embodiment comprises the following raw materials in parts by weight:
[0036] 35-40 parts of natural rubber, 10-15 parts of multi-adjusting balance agent, 4-7 parts of modified filler, 5-8 parts of carbon black N330, 3-5 parts of silane coupling agent, 2-4 parts of sulfur, 1-3 parts of accelerator, 1-3 parts of stearic acid, and 1-3 parts of antioxidant.
[0037] The natural rubber in this embodiment is No. 3 smoked rubber; the silane coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 4020; and the accelerator is accelerator TMTD.
[0038] The preparation method of the multi-adjusting balancing agent of this embodiment is:
[0039] S01: Stir and mix the nano-attapulgite in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry to obtain dry nano-attapulgite;
[0040] The dried nano-attapulgite is calcined at 220-230° C. for 20-30 min, then cooled to 55° C. at a rate of 2-5° C. / min, and kept warm to obtain calcined nano-attapulgite;
[0041] S02: Add 3-5 parts of nano titanium dioxide and 1-2 parts of carboxymethyl cellulose to 5-8 parts of modified chitosan agent by weight, and then add 2-4 parts of wollastonite, and blend them well to achieve coordination;
[0042] Wherein, the preparation method of modified chitosan agent is:
[0043] A chitosan solution with a mass fraction of 3-6% is prepared, and a sodium silicate solution with a mass fraction of 4-7% of the total weight of the chitosan solution and a sodium lignin sulfonate with a mass fraction of 2-4% of the total weight of the chitosan solution are added to the chitosan solution and mixed sufficiently to obtain a modified chitosan agent;
[0044] S03: The calcined nano-attapulgite and blending agent are ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1200-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a multi-tuning balancing agent.
[0045] The mass fraction of the sodium silicate solution in this embodiment is 5-7%.
[0046] The preparation method of the modified filler of this embodiment is:
[0047] S11: The nano-calcium carbonate is firstly mixed in a 5% sodium citrate solution having a mass fraction of 3 to 5 times the total weight of the nano-calcium carbonate, to obtain a nano-calcium carbonate solution;
[0048] S12: adding 2 to 3 parts of nano-silica sol and 1 to 3 parts of silane coupling agent to 5 to 8 parts of lanthanum nitrate solution by weight, stirring and blending them thoroughly to obtain a modified silica sol;
[0049] The nano calcium carbonate solution and the modified silica sol agent are uniformly mixed in a weight ratio of 5:(2-3) to obtain a nano calcium carbonate modifier;
[0050] S13: The nano calcium carbonate modifier and the reinforcing agent are mixed and ball-milled in a weight ratio of 5:3, with a ball-milling speed of 1000-1050 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a modified filler.
[0051] The mass fraction of the lanthanum nitrate solution in this embodiment is 3-5%; the silane coupling agent is silane coupling agent KH560.
[0052] The preparation method of the reinforcing agent of this embodiment is:
[0053] According to weight, 2-5 parts of calcined talcum powder and 1-3 parts of stearic acid are added to 5-8 parts of dopamine hydrochloride solution, and then 2-3 parts of silicon nitride whiskers and 1-2 parts of yttrium nitrate solution are added and mixed and ball-milled at a speed of 750-850 r / min for 2 hours. After the ball milling is completed, the reinforcing agent is washed with water, filtered and dried to obtain the reinforcing agent.
[0054] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3-6%; the mass fraction of the yttrium nitrate solution is 3-5%.
[0055] A method for preparing a rubber for a diamond wire saw according to the present embodiment is used to prepare the rubber for a diamond wire saw, and comprises the following steps:
[0056] The raw materials are weighed according to weight, and then the raw materials are mixed at a mixing temperature of 45° C. for 20 minutes. After the mixing is completed, a mixed material is obtained; the mixed material is placed in a vulcanizer for vulcanization at a vulcanization temperature of 145° C., a vulcanization pressure of 10-15 MPa, and a vulcanization time of 6-10 minutes to obtain a rubber for a diamond wire saw.
[0057] A diamond wire saw of this embodiment includes the above-mentioned rubber for diamond wire saw.
[0058] Embodiment 1: A rubber for diamond wire saw, comprising the following raw materials in parts by weight:
[0059] 35 parts of natural rubber, 10 parts of multi-adjusting balancer, 4 parts of modified filler, 5 parts of carbon black N330, 3 parts of silane coupling agent, 2 parts of sulfur, 1 part of accelerator, 1 part of stearic acid, and 1 part of antioxidant.
[0060] The natural rubber in this embodiment is No. 3 smoked rubber; the silane coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 4020; and the accelerator is accelerator TMTD.
[0061] The preparation method of the multi-adjusting balancing agent of this embodiment is:
[0062] S01: Stir and mix the nano-attapulgite in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry to obtain dry nano-attapulgite;
[0063] The dried nano-attapulgite was calcined at 220° C. for 20 min, then cooled to 55° C. at a rate of 2° C. / min, and kept warm to obtain calcined nano-attapulgite;
[0064] S02: Add 3 parts of nano titanium dioxide and 1 part of carboxymethyl cellulose to 5 parts of modified chitosan agent by weight, and then add 2 parts of wollastonite, and blend them thoroughly to achieve a harmonious harmony;
[0065] Wherein, the preparation method of modified chitosan agent is:
[0066] A chitosan solution with a mass fraction of 3% is prepared, and a sodium silicate solution with a mass fraction of 4% of the total weight of the chitosan solution and a sodium lignin sulfonate with a mass fraction of 2% of the total weight of the chitosan solution are added to the chitosan solution and mixed thoroughly to obtain a modified chitosan agent;
[0067] S03: The calcined nano-attapulgite and the blending agent are subjected to ball milling treatment in a weight ratio of 5:3, the ball milling speed is 1200r / min, and the ball milling is performed for 2h. After the ball milling is completed, the mixture is washed with water and dried to obtain a multi-adjusting balancing agent.
[0068] The mass fraction of the sodium silicate solution in this embodiment is 5%.
[0069] The preparation method of the modified filler of this embodiment is:
[0070] S11: The nano-calcium carbonate is firstly mixed in a 5% sodium citrate solution having a mass fraction of 3 times the total weight of the nano-calcium carbonate, to obtain a nano-calcium carbonate solution;
[0071] S12: adding 2 parts of nano-silica sol and 1 part of silane coupling agent to 5 parts of lanthanum nitrate solution by weight, stirring and blending them thoroughly to obtain a modified silica sol;
[0072] The nano calcium carbonate solution and the modified silica sol are uniformly mixed in a weight ratio of 5:2 to obtain a nano calcium carbonate modifier;
[0073] S13: The nano-calcium carbonate modifier and the reinforcing agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.
[0074] The mass fraction of the lanthanum nitrate solution in this embodiment is 3%; the silane coupling agent is silane coupling agent KH560.
[0075] The preparation method of the reinforcing agent of this embodiment is:
[0076] According to weight, 2 parts of calcined talcum powder and 1 part of stearic acid are added to 5 parts of dopamine hydrochloride solution, and then 2 parts of silicon nitride whiskers and 1 part of yttrium nitrate solution are added and mixed and ball-milled at a speed of 750 r / min for 2 hours. After the ball milling is completed, the reinforcing agent is washed with water, filtered and dried to obtain a reinforcing agent.
[0077] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3%; the mass fraction of the yttrium nitrate solution is 3%.
[0078] A method for preparing a rubber for a diamond wire saw according to the present embodiment is used to prepare the rubber for a diamond wire saw, and comprises the following steps:
[0079] The raw materials are weighed according to weight, and then the raw materials are mixed at a mixing temperature of 45° C. for 20 minutes. After the mixing is completed, a mixed material is obtained; the mixed material is placed in a vulcanizer for vulcanization to obtain the rubber for diamond wire saw of the present invention; the vulcanization temperature is 145° C., the vulcanization pressure is 10 MPa, and the vulcanization time is 6 minutes.
[0080] A diamond wire saw of this embodiment includes the above-mentioned rubber for diamond wire saw.
[0081] Embodiment 2: A rubber for diamond wire saw, comprising the following raw materials in parts by weight:
[0082] 40 parts of natural rubber, 15 parts of multi-adjusting balancer, 7 parts of modified filler, 8 parts of carbon black N330, 5 parts of silane coupling agent, 4 parts of sulfur, 3 parts of accelerator, 3 parts of stearic acid, and 3 parts of antioxidant.
[0083] The natural rubber in this embodiment is No. 3 smoked rubber; the silane coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 4020; and the accelerator is accelerator TMTD.
[0084] The preparation method of the multi-adjusting balancing agent of this embodiment is:
[0085] S01: Stir and mix the nano-attapulgite in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry to obtain dry nano-attapulgite;
[0086] The dried nano-attapulgite was calcined at 230° C. for 30 min, then cooled to 55° C. at a rate of 5° C. / min, and kept warm to obtain calcined nano-attapulgite;
[0087] S02: Add 5 parts of nano titanium dioxide and 2 parts of carboxymethyl cellulose to 8 parts of modified chitosan agent by weight, and then add 4 parts of wollastonite, and blend them thoroughly to achieve a harmonious harmony;
[0088] Wherein, the preparation method of modified chitosan agent is:
[0089] A chitosan solution with a mass fraction of 6% is prepared, and a sodium silicate solution with a mass fraction of 7% of the total weight of the chitosan solution and a sodium lignin sulfonate with a mass fraction of 4% of the total weight of the chitosan solution are added to the chitosan solution and mixed thoroughly to obtain a modified chitosan agent;
[0090] S03: The calcined nano-attapulgite and the blending agent are subjected to ball milling treatment in a weight ratio of 5:3, the ball milling speed is 1500r / min, and the ball milling is performed for 2h. After the ball milling is completed, the mixture is washed with water and dried to obtain a multi-adjusting balancing agent.
[0091] The mass fraction of the sodium silicate solution in this embodiment is 7%.
[0092] The preparation method of the modified filler of this embodiment is:
[0093] S11: The nano-calcium carbonate is firstly mixed in a 5% sodium citrate solution having a mass fraction of 5 times the total weight of the nano-calcium carbonate, to obtain a nano-calcium carbonate solution;
[0094] S12: adding 3 parts of nano silica sol and 3 parts of silane coupling agent to 8 parts of lanthanum nitrate solution by weight, stirring and blending them thoroughly to obtain a modified silica sol;
[0095] The nano calcium carbonate solution and the modified silica sol are uniformly mixed in a weight ratio of 5:3 to obtain a nano calcium carbonate modifier;
[0096] S13: The nano-calcium carbonate modifier and the reinforcing agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1050 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.
[0097] The mass fraction of the lanthanum nitrate solution in this embodiment is 5%; the silane coupling agent is silane coupling agent KH560.
[0098] The preparation method of the reinforcing agent of this embodiment is:
[0099] According to weight, 5 parts of calcined talcum powder and 3 parts of stearic acid are added to 8 parts of dopamine hydrochloride solution, and then 3 parts of silicon nitride whiskers and 2 parts of yttrium nitrate solution are added and mixed and ball-milled at a speed of 850 r / min for 2 hours. After the ball milling is completed, the reinforcing agent is washed with water, filtered and dried to obtain a reinforcing agent.
[0100] The mass fraction of the dopamine hydrochloride solution in this embodiment is 6%; the mass fraction of the yttrium nitrate solution is 5%.
[0101] A method for preparing a rubber for a diamond wire saw according to the present embodiment is used to prepare the rubber for a diamond wire saw, and comprises the following steps:
[0102] The raw materials are weighed according to weight, and then the raw materials are mixed at a mixing temperature of 45° C. for 20 minutes. After the mixing is completed, a mixed material is obtained; the mixed material is placed in a vulcanizer for vulcanization to obtain the rubber for diamond wire saw of the present invention; the vulcanization temperature is 145° C., the vulcanization pressure is 15 MPa, and the vulcanization time is 10 minutes.
[0103] A diamond wire saw of this embodiment includes the above-mentioned rubber for diamond wire saw.
[0104] Embodiment 3: A rubber for diamond wire saw, comprising the following raw materials in parts by weight:
[0105] 37.5 parts of natural rubber, 12.5 parts of multi-adjusting balancer, 5.5 parts of modified filler, 6.5 parts of carbon black N330, 4 parts of silane coupling agent, 3 parts of sulfur, 2 parts of accelerator, 2 parts of stearic acid, and 2 parts of antioxidant.
[0106] The natural rubber in this embodiment is No. 3 smoked rubber; the silane coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 4020; and the accelerator is accelerator TMTD.
[0107] The preparation method of the multi-adjusting balancing agent of this embodiment is:
[0108] S01: Stir and mix the nano-attapulgite in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry to obtain dry nano-attapulgite;
[0109] The dried nano-attapulgite was calcined at 225° C. for 25 min, then cooled to 55° C. at a rate of 3.5° C. / min, and kept warm to obtain calcined nano-attapulgite;
[0110] S02: According to weight, 4 parts of nano titanium dioxide and 1.5 parts of carboxymethyl cellulose are added to 6.5 parts of modified chitosan agent, and then 3 parts of wollastonite are added, and the mixture is fully blended to obtain a blending synergist;
[0111] Wherein, the preparation method of modified chitosan agent is:
[0112] A chitosan solution with a mass fraction of 4.5% is prepared, and a sodium silicate solution with a mass fraction of 5.5% of the total weight of the chitosan solution and a sodium lignin sulfonate with a mass fraction of 3% of the total weight of the chitosan solution are added to the chitosan solution and mixed thoroughly to obtain a modified chitosan agent;
[0113] S03: The calcined nano-attapulgite and the blending synergist are ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1350 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a multi-tuning balancing agent.
[0114] The mass fraction of the sodium silicate solution in this embodiment is 6%.
[0115] The preparation method of the modified filler of this embodiment is:
[0116] S11: The nano-calcium carbonate is firstly mixed in a 5% sodium citrate solution having a mass fraction of 4 times the total weight of the nano-calcium carbonate, to obtain a nano-calcium carbonate solution;
[0117] S12: adding 2.5 parts of nano-silica sol and 2 parts of silane coupling agent to 6.5 parts of lanthanum nitrate solution by weight, stirring and blending them thoroughly to obtain a modified silica sol;
[0118] The nano calcium carbonate solution and the modified silica sol agent are uniformly mixed in a weight ratio of 5:2.5 to obtain a nano calcium carbonate modifier;
[0119] S13: The nano-calcium carbonate modifier and the reinforcing agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1025 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a modified filler.
[0120] The mass fraction of the lanthanum nitrate solution in this embodiment is 4%; the silane coupling agent is silane coupling agent KH560.
[0121] The preparation method of the reinforcing agent of this embodiment is:
[0122] According to weight, 3.5 parts of calcined talcum powder and 2 parts of stearic acid are added to 6.5 parts of dopamine hydrochloride solution, and then 2.5 parts of silicon nitride whiskers and 1.5 parts of yttrium nitrate solution are added and mixed and ball-milled at a speed of 800 r / min for 2 hours. After the ball milling is completed, the reinforcing agent is washed with water, filtered and dried.
[0123] The mass fraction of the dopamine hydrochloride solution in this embodiment is 4.5%; the mass fraction of the yttrium nitrate solution is 4%.
[0124] A method for preparing a rubber for a diamond wire saw according to the present embodiment is used to prepare the rubber for a diamond wire saw, and comprises the following steps:
[0125] The raw materials are weighed according to weight, and then the raw materials are mixed at a mixing temperature of 45° C. for 20 minutes. After the mixing is completed, a mixed material is obtained; the mixed material is placed in a vulcanizer for vulcanization to obtain the rubber for diamond wire saw of the present invention; the vulcanization temperature is 145° C., the vulcanization pressure is 12.5 MPa, and the vulcanization time is 8 minutes.
[0126] A diamond wire saw of this embodiment includes the above-mentioned rubber for diamond wire saw.
[0127] Comparative Example 1:
[0128] The difference from Example 3 is that no multi-adjusting balancing agent is added.
[0129] Comparative Example 2:
[0130] The difference from Example 3 is that step S01 is not used in the preparation of the multi-adjusting balancing agent.
[0131] Comparative Example 3:
[0132] The difference from Example 3 is that no synergist treatment is used in the preparation of the multi-adjusting balancing agent.
[0133] Comparative Example 4:
[0134] The difference from Example 3 is that nano titanium dioxide and wollastonite are not added in the preparation of the blending synergist.
[0135] Comparative Example 5:
[0136] The difference from Example 3 is that the modified chitosan agent in the preparation of the blending synergist is replaced by a chitosan solution with a mass fraction of 4.5%.
[0137] Comparative Example 6:
[0138] The difference from Example 3 is that no modified filler is added.
[0139] Comparative Example 7:
[0140] The difference from Example 3 is that no nano calcium carbonate modifier is added in the preparation of the modified filler.
[0141] Comparative Example 8:
[0142] The difference from Example 3 is that no modified silica sol is added in the preparation of the nano calcium carbonate modifier.
[0143] Comparative Example 9:
[0144] The difference from Example 3 is that the modified silica sol agent is replaced by nano silica sol.
[0145] Comparative Example 10:
[0146] The difference from Example 3 is that no reinforcing agent is added in the preparation of the modified filler.
[0147] The products of Examples 1 to 3 and Comparative Examples 1 to 10 were subjected to conventional performance tests. At the same time, the products were placed at 70°C for 12 hours, then at -5°C for 12 hours, and the products were placed under 2% hydrochloric acid mist conditions for 12 hours. The above was a cycle and the test was repeated 10 times to test the cold and heat resistance and acid mist resistance stability. The test results are shown in Table 1.
[0148] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 10:
[0149]
[0150] From the test results of the products of Examples 1 to 3 and Comparative Examples 1 to 10, it can be seen that the product of Example 3 has excellent wear resistance, tear resistance and flexural properties, and the three properties are improved in a coordinated manner, and the product has significant effects on cold and heat resistance and acid corrosion resistance stability;
[0151] The present invention does not add any of the multi-adjusting balancing agent and the modified filler, and the performance coordination and performance stability of the product show a significant trend of deterioration. The performance effect of the product is most significant by using the coordination and synergy of the two.
[0152] The performance of the product also showed a trend of deterioration when the S01 step was not used in the preparation of the multi-adjustment balancing agent, the blending synergist was not used in the preparation of the multi-adjustment balancing agent, nano titanium dioxide and wollastonite were not added in the preparation of the blending synergist, and the modified chitosan agent was replaced by a chitosan solution with a mass fraction of 4.5% in the preparation of the blending synergist. The multi-adjustment balancing agent obtained by the specific method of the present invention had the most obvious product performance effect;
[0153] The performance of the products showed different degrees of deterioration when no nano-calcium carbonate modifier was added in the preparation of the modified filler, no modified silica sol was added in the preparation of the nano-calcium carbonate modifier, nano-silica sol was used to replace the modified silica sol, and no reinforcing agent was added in the preparation of the modified filler. The performance of the product deteriorated significantly when no reinforcing agent was added in the preparation of the modified filler. The specific nano-calcium carbonate modifier of the present invention was used to achieve the most obvious product performance effect.
[0154] The present invention further explores the product performance through the preparation of a reinforcing agent.
[0155] Experimental Example 1:
[0156] The only difference from Example 3 is that no calcined talc is added in the preparation of the reinforcing agent.
[0157] Experimental Example 2:
[0158] The only difference from Example 3 is that silicon nitride whiskers are not added in the preparation of the reinforcing agent.
[0159] Experimental Example 3:
[0160] The only difference from Example 3 is that no yttrium nitrate solution and stearic acid are added in the preparation of the reinforcing agent.
[0161] Experimental Example 4:
[0162] The only difference from Example 3 is that no dopamine hydrochloride solution is added during the preparation of the reinforcing agent.
[0163] Experimental Example 5:
[0164] The only difference from Example 3 is that the mass fraction of the dopamine hydrochloride solution is 7%; the mass fraction of the yttrium nitrate solution is 6%.
[0165] The products of Experimental Examples 1 to 5 were subjected to conventional performance tests. At the same time, the products were placed at 70°C for 12 hours, then at -5°C for 12 hours, and the products were placed under 2% hydrochloric acid mist conditions for 12 hours. The above was a cycle and the test was repeated 10 times to test the cold and heat resistance and acid mist resistance stability. The test results are shown in Table 2.
[0166] Table 2 Product performance test results of Experimental Examples 1 to 5:
[0167]
[0168] It can be seen from Experimental Examples 1-5 that silicon nitride whiskers are not added in the preparation of the reinforcing agent, and the performance of the product changes. Among the factors in the preparation of the reinforcing agent, the performance deterioration is the most obvious, followed by the absence of calcined talcum powder, and the absence of yttrium nitrate solution and stearic acid in the preparation of the reinforcing agent. The performance of the product has a tendency to deteriorate. In addition, dopamine hydrochloride solution is not added in the preparation of the reinforcing agent, and the mass fraction of dopamine hydrochloride solution is 7%; the mass fraction of the yttrium nitrate solution is 6%, and the performance of the product also shows a tendency to deteriorate. Changes in the mass fraction of the product raw materials will also lead to deterioration of the product performance. The reinforcing agents obtained by different methods have a tendency to deteriorate in product performance. Only the reinforcing agent obtained by the method of the present invention has the most significant product performance effect.
[0169] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0170] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A rubber for diamond wire saw, characterized in that: It includes the following raw materials in parts by weight: 35-40 parts of natural rubber, 10-15 parts of multi-adjusting balance agent, 4-7 parts of modified filler, 5-8 parts of carbon black N330, 3-5 parts of silane coupling agent, 2-4 parts of sulfur, 1-3 parts of accelerator, 1-3 parts of stearic acid, 1-3 parts of antioxidant; The preparation method of the multi-adjusting balancing agent is: S01: Stir and mix the nano-attapulgite in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry to obtain dry nano-attapulgite; The dried nano-attapulgite is calcined at 220-230° C. for 20-30 min, then cooled to 55° C. at a rate of 2-5° C. / min, and kept warm to obtain calcined nano-attapulgite; S02: Add 3-5 parts of nano titanium dioxide and 1-2 parts of carboxymethyl cellulose to 5-8 parts of modified chitosan agent by weight, and then add 2-4 parts of wollastonite, and mix well to obtain a blending synergist; Wherein, the preparation method of modified chitosan agent is: A chitosan solution with a mass fraction of 3-6% is prepared, and a sodium silicate solution with a mass fraction of 4-7% of the total weight of the chitosan solution and a sodium lignin sulfonate with a mass fraction of 2-4% of the total weight of the chitosan solution are added to the chitosan solution and mixed sufficiently to obtain a modified chitosan agent; S03: The calcined nano-attapulgite and the blending synergist are ball-milled in a weight ratio of 5:3, the ball-milling speed is 1200-1500 r / min, the ball-milling is performed for 2 h, and after the ball-milling is completed, the mixture is washed with water and dried to obtain a multi-adjusting balancing agent; The preparation method of the modified filler is: S11: The nano-calcium carbonate is firstly mixed in a 5% sodium citrate solution having a mass fraction of 3 to 5 times the total weight of the nano-calcium carbonate, to obtain a nano-calcium carbonate solution; S12: adding 2 to 3 parts of nano-silica sol and 1 to 3 parts of silane coupling agent to 5 to 8 parts of lanthanum nitrate solution by weight, stirring and blending them thoroughly to obtain a modified silica sol; The nano calcium carbonate solution and the modified silica sol are uniformly mixed in a weight ratio of 5:(2-3) to obtain a nano calcium carbonate modifier; S13: mixing the nano calcium carbonate modifier and the reinforcing agent in a weight ratio of 5:3 and subjecting the mixture to ball milling at a speed of 1000-1050 r / min for 1 h. After the ball milling is completed, washing, filtering and drying are performed to obtain a modified filler; The preparation method of the reinforcing agent is: According to weight, 2-5 parts of calcined talcum powder and 1-3 parts of stearic acid are added to 5-8 parts of dopamine hydrochloride solution, and then 2-3 parts of silicon nitride whiskers and 1-2 parts of yttrium nitrate solution are added and mixed and ball-milled at a speed of 750-850 r / min for 2 hours. After the ball milling is completed, the reinforcing agent is washed with water, filtered and dried to obtain the reinforcing agent.
2. The rubber for diamond wire saw according to claim 1, characterized in that: The natural rubber is No. 3 smoked rubber; the silane coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 4020; and the accelerator is accelerator TMTD.
3. The rubber for diamond wire saw according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 5-7%.
4. The rubber for diamond wire saw according to claim 1, characterized in that: The mass fraction of the lanthanum nitrate solution is 3-5%; the silane coupling agent is silane coupling agent KH560.
5. The rubber for diamond wire saw according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 3-6%; the mass fraction of the yttrium nitrate solution is 3-5%.
6. A method for preparing a rubber for a diamond wire saw, for preparing the rubber for a diamond wire saw as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The raw materials are weighed according to weight, and then the raw materials are mixed at a mixing temperature of 45° C. for 20 minutes. After the mixing is completed, a mixed material is obtained; the mixed material is placed in a vulcanizer for vulcanization at a vulcanization temperature of 145° C., a vulcanization pressure of 10-15 MPa, and a vulcanization time of 6-10 minutes to obtain a rubber for a diamond wire saw.
7. A diamond wire saw, comprising the rubber for a diamond wire saw according to any one of claims 1 to 5.
Citation Information
Patent Citations
Diamond wire saw rubber for injection and preparation method thereof
CN118185138A